Efficacy of trimetazidine for myocardial ischemia-reperfusion injury in rat models: a systematic review and meta-analysis - Xiaobin Zhang; Zhanhui Duan; Yanpu Yu; Chunjing Li; Mingyao Hao; Yuning Ma; Yuxia Ma; Dongqing Du (PeerJ)
Context Trimetazidine (TMZ) is used as a medication for ischemic heart disease treatment. Recently, several animal models have been studied in relation to the research on myocardial ischemia-reperfusion injury (MIRI) treatment. In this study, we conducted a meta-analysis of TMZ in rat MIRI models to evaluate TMZ’s therapeutic efficacy. Methods We systematically searched eight databases for studies on TMZ in rat MIRI models. We utilized two literature quality assessment criteria to evaluate the paper quality. Assessment of TMZ treatment efficacy was based on the outcomes, as well as on the subgroup analysis. This study was registered at PROSPERO (registration number CRD42022377728). Results After applying the inclusion and exclusion criteria, 24 eligible studies were shortlisted from 405 studies. We found that, in rat MIRI models, TMZ dramatically boosted the superoxide dismutase (SOD) levels while decreasing the levels of malondialdehyde (MDA), lactate dehydrogenase (LDH), and creatine kinase isoenzyme (CK-MB), and the infarct size. In addition, the duration of myocardial ischemia, reperfusion duration, dosage, rat species and mode of administration influenced the effectiveness of TMZ. The result indicated that TMZ had a considerable therapeutic effect on the duration of myocardial ischemia at less than 30 min as well as on the duration of reperfusion at 120–180 min. In fact, it was more effective when administered intravenously and via gavage at doses of 3–10 mg/kg. Conclusion TMZ can attenuate the damage caused by MIRI in rat, with a myocardial protective effect. These findings would facilitate preclinical evidence for further investigation.